Isolated hepatic sarcoidosis - Jovičić, Ivana; Popović, Dušan Dj.; Tončev, Ljubiša; Jovičić, Žikica; Vučinić, Violeta; Kovačević, Nada; Djuranović, Srdjan; Boričić, Ivan; Micev, Marjan; Špuran, Milan; Milosavljević, Tomica (Vojnosanitetski pregled, 2014)
Introduction. Sarcoidosis is a multisystem granulomatous disease of unknown etiology. Although hepatic granulomas occur in 50–65% of patients with systemic sarcoidosis, isolated liver sarcoidosis is rare. Clinical presentation varies from asymptomatic to manifest. The diagnosis is based on a characteristic histopathological finding of liver biopsy. Case report. We reported a 69-year old man was admitted due to abdominal swelling and abdominal pain. Laboratory studies detected: cholestasis, pancytopenia and elevaton of angiotensin-converting enzyme. Abdominal imaging techniques showed liver cirrhosis, splenomegaly and ascites. The diagnosis of the hepatic sarcoidosis was confirmed by histopathological examination of liver biopsy. The patient was treated with corticosteroids. After 18 months the patient was without any subjective symptoms, and with biochemical and clinical improvement. Conclusion. Isolated hepatic sarcoidosis should be considered in the differential diagnosis of asymptomatic or simptomatic patients with hepatosplenomegaly and changes in liver functional tests. Only the timely diagnosis and proper treatment can lead to subjective and objective improvement of patients.
Keywords: sarcoidosis; liver cirrhosis; splenomegaly; ascites; diagnosis; histological techniques; treatment outcome